[Alpha] 5 [beta] 1-integrin and MT1-MMP promote tumor cell migration in 2D but not in 3D fibronectin microenvironments - Corall, Silke Melanie; Haraszti, Tamás; Bartoschik, Tanja; Spatz, Joachim P.; Ludwig, Thomas; Cavalcanti-Adam, Elisabetta A. (Computational mechanics, 2014)
Cell migration is a crucial event for physiological processes, such as embryonic development and wound healing, as well as for pathological processes, such as cancer dissemination and metastasis formation. Cancer cell migration is a result of the concerted action of matrix metalloproteinases (MMPs), expressed by cancer cells to degrade the surrounding matrix, and integrins, the transmembrane receptors responsible for cell binding to matrix proteins. While it is known that cell-microenvironment interactions are essential for migration, the role of the physical state of such interactions remains still unclear. In this study we investigated human fibrosarcoma cell migration in two-dimensional (2D) and three-dimensional (3D) fibronectin (FN) microenvironments. By using antibody blocking approach and cell-binding site mutation, we determined that $$\upalpha _{5}\upbeta _{1}$$α5β1-integrin is the main mediator of fibrosarcoma cell migration in 2D FN, whereas in 3D fibrillar FN, the binding of $$\upalpha _{5}\upbeta _{1}$$α5β1- and $$\upalpha _v\upbeta _{3}$$αvβ3-integrins is not necessary for cell movement in the fibrillar network. Furthermore, while the general inhibition of MMPs with GM6001 has no effect on cell migration in both 2D and 3D FN matrices, we observed opposing effect after targeted silencing of a membrane-bound MMP, namely MT1-MMP. In 2D fibronectin, silencing of MT1-MMP results in decreased migration speed and loss of directionality, whereas in 3D FN matrices, cell migration speed is increased and integrin-mediated signaling for actin dynamics is promoted. Our results suggest that the fibrillar nature of the matrix governs the migratory behavior of fibrosarcoma cells. Therefore, to hinder migration and dissemination of diseased cells, matrix molecules should be directly targeted, rather than specific subtypes of receptors at the cell membrane.
Im Titel sind "alpha" und "beta" als griechische Buchstaben dargestellt
Gesehen am 22.09.2020